System-wide analyses reveal essential roles of N-terminal protein modification in bacterial membrane integrity - Chien-I Yang; Zikun Zhu; Jeffrey J. Jones; Brett Lomenick; Tsui-Fen Chou; Shu-ou Shan (iScience, 2022)
Summary: The removal of the N-terminal formyl group on nascent proteins by peptide deformylase (PDF) is the most prevalent protein modification in bacteria. PDF is a critical target of antibiotic development; however, its role in bacterial physiology remains a long-standing question. This work used the time-resolved analyses of the Escherichia coli translatome and proteome to investigate the consequences of PDF inhibition. Loss of PDF activity rapidly induces cellular stress responses, especially those associated with protein misfolding and membrane defects, followed by a global down-regulation of metabolic pathways. Rapid membrane hyperpolarization and impaired membrane integrity were observed shortly after PDF inhibition, suggesting that the plasma membrane disruption is the most immediate and primary consequence of formyl group retention on nascent proteins. This work resolves the physiological function of a ubiquitous protein modification and uncovers its crucial role in maintaining the structure and function of the bacterial membrane.